Perlindungan Batasan Kebebasan Berwasiat: Analisis Legitieme Portie dalam Hukum Perdata Indonesia - Amaliah, Amaliah; Marniati, Felicitas Sri; Lontoh, Rielly (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2025)
Article 875 of the Civil Code stipulates that a will expresses the testator’s wishes regarding beneficiaries and becomes effective after death. However, such provisions must not contravene Article 913, which guarantees the absolute rights (legitieme portie) of heirs. This study examines two issues: the legal consequences of a will addressed to a specific legitimary and the legal protection afforded to a legitimary when a will favors another beneficiary. The research employs a normative juridical method, using statutory, conceptual, analytical, and case study approaches, with data drawn from legal literature and legislation. Analysis was conducted through grammatical interpretation, analogical construction, and legal refinement. The findings show that a will directed to a particular legitimary has no unique legal consequences, since a will may designate any person as beneficiary. Nonetheless, the legitieme portie must not be impaired, as it constitutes a protected right under Articles 913 and 914 of the Civil Code. This protection applies from the opening of inheritance. The study underscores that while testamentary freedom is recognized, it is limited by the inviolable rights of legitimaries, ensuring fairness and legal certainty in inheritance law.